PENGEMBARAAN AKUNTAN MENUJU KESADARAN SPIRITUAL: DILIHAT DARI PERSPEKTIF ONTOLOGI, EPISTEMOLOGI, DAN AKSIOLOGI - Leniwati, Driana (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2019)
Modern accounting that emphasizes material and value-free makes accounting toward materialistic, selfish, secularistic and atheistic. This is proven by the many cases of irregularities and manipulations of financial statements carried out by accountants that reflect those characteristics. Meanwhile human assumptions as an opportunistic, greedy and selfish homo economicus increasing this phenomenon. This become the big question to accounting science and the nature of accountants. Accounting as a branch of science has far away from the philosophy. The foothold of the science of accounting is to achieve the true nature of science and attain the ultimate truth of science. This study aims to review accounting from the perspective of ontology, epistemology, axiology and synergize the self-awareness of accountants in relation to humans, nature and God will bring accounting knowledge back to its essence and accountant to God so that accounting science will give benefit to humanity.Â